The impacts of corporate social responsibility to corporate financial performance: A case study of Vietnamese commercial banks - Thich Van Nguyen; Hang T.T. Bui; Chi H.D. Le (Cogent Economics & Finance)
This study aims to investigate the relationship between corporate social responsibility (CSR) and corporate financial performance (CFP). A multi-method approach has been applied to measure CSR. Net interest margin (NIM), return on assets (ROA), and return on equity (ROE) are selected to represent the financial performance of the bank. Using a sample of Vietnamese commercial banks from 2012 to 2019 to perform regressions in the dynamic panel models with the two-step system generalized method of moments (GMM) estimator, the results show a positive effect of both corporate social responsibility expenditure (CSRE) and corporate social responsibility disclosure (CSRD) on the financial performance of the bank. The results also show the impact of the component CSRs on the bank’s financial performance, particularly finding a positive effect of Environmental responsibility and Employee responsibility. In contrast, the influence of Community responsibility is not evident.